Geology and a land use and land cover classification system for use with remote sensor data of Kuala Tiga, Tanah Merah - Zuhaira Nadhila Zahuri (2017)
Land use and land cover classification system has been used widely in many applications such as for baseline mapping for GIS input and also target identification for identification of roads, clearings and also land and water interface. The research was conducted in Kuala Tiga, Tanah Merah, Kelantan with entitled geology and a land use and land cover classification system for use with remote sensor data. The study area covers for about 25 km². The purpose of this paper are 1) to produce geological map of the study area in scale 1: 25 000, 2) to access the possibilities of using remote sensing for the detection of regional land use change by developing land cover classification system, 3) to compare the accuracy of supervised and unsupervised classification system by using remote sensing. In this research, the methods that have been used were geological mapping, petrographic analysis and both supervised and unsupervised classification that were tested on satellite images of Landsat 7 and 8 in the year 2001 and 2016.